(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the influence of sending text messages via a communication application on the compliance of young patients undergoing orthodontic treatment by determining the number of orthodontic bracket failures. Materials and methods: A sample comprising 54 patients (mean age, 14.7 years) undergoing orthodontic treatment was divided into two groups of 27 patients each: the experimental group (age, 15.11 ± 2.69 years) and the control group (age, 15.44 ± 2.69 years). For four months, weekly messages were sent via the communication application WhatsApp directly to the cellphones of patients in the experimental group, encouraging them to follow instructions for avoiding bracket failures in the initial phase of the orthodontic treatment. At the end of four months, the number of bracket failures were compared between the groups. Fisher’s exact test was used to compare the number of patients who had a failure. The “chi-square” test was used to evaluate the number of number of bracket failures. We adopted a significance level of 5% (P<.05). Results: There was no statistically significant difference between the experimental and control groups, although the number of failed brackets was higher in the control group. Conclusion: Sending messages via a communication application did not influence the number of bracket failures in young patients undergoing orthodontic treatment.